Network meta‐analysis of medical therapy efficacy in more than 90,000 patients with heart failure and reduced ejection fraction - De Marzo, Vincenzo; Savarese, Gianluigi; Tricarico, Lucia; Hassan, Sofia; Iacoviello, Massimo; Porto, Italo; Ameri, Pietro (Journal of internal medicine, 2022)
Background Following the availability of new drugs for chronic heart failure (HF) with reduced ejection fraction (HFrEF), we sought to provide an updated and comparative synthesis of the evidence on HFrEF pharmacotherapy efficacy. Methods We performed a Bayesian network meta‐analysis of phase 2 and 3 randomized controlled trials (RCTs) of medical therapy in HFrEF patient cohorts with more than 90% of the participants with left ventricular ejection fraction less than 45% and all‐cause mortality reported. Results Sixty‐nine RCTs, accounting for 91,741 subjects, were evaluated. The step‐wise introduction of new drugs progressively decreased the risk of all‐cause death, up to reaching a random‐effects hazard ratio (HR) of 0.43 (95% credible intervals [CrI] 0.27–0.63) with beta blockers (BB), angiotensin‐converting enzyme inhibitors (ACEi), and mineralocorticoid receptor antagonist (MRA) versus placebo. The risk was further reduced by adding sodium–glucose cotransporter‐2 inhibitors (SGLT2i; HR 0.38, 95% CrI 0.22–0.60), ivabradine (HR 0.39, 95% CrI 0.21–0.64), or vericiguat (HR 0.40, 95% CrI 0.22–0.65) to neurohormonal inhibitors, and by angiotensin receptor–neprilysin inhibitor (ARNI), BB, and MRA (HR 0.36, 95% CrI 0.20–0.60). In a sensitivity analysis considering the ARNI and non‐ARNI subgroups of SGLT2i RCTs, the combination SGLT2i + ARNI + BB + MRA was associated with the lowest HR (0.28, 95% CrI 0.16–0.45 vs. 0.40, 95% CrI 0.24–0.60 for SGLT2i + BB + ACEi + MRA). Consistent results were obtained in sensitivity analyses and by calculating surface under the cumulative ranking area, as well as for cardiovascular mortality (information available for 56 RCTs), HF hospitalization (45 RCTs), and all‐cause hospitalization (26 RCTs). Conclusions Combination medical therapy including neurohormonal inhibitors and newer drugs, especially ARNI and SGLT2i, confers the maximum benefit with regard to HFrEF prognosis.